CD4 and CD8 monoclonal antibody therapy: strategies to prolong renal allograft survival in the dog. - Watson, C; Cobbold, S; Davies, H; Rebello, P; Waldmann, H; Calne, R; Metcalfe, S (1993)
The value of CD4 and CD8 monoclonal antibody therapy in tolerance induction has been demonstrated in rodent transplant models. In this paper the immunosuppressive potential of CD4 and CD8 monoclonal antibodies for dog renal allografts was evaluated as a preliminary to tolerogenic studies in this large animal model. Monoclonal antibodies were given for a maximum of 10 days after transplantation. Therapy was stopped prematurely following adverse reactions associated with the recipient developing an antibody response against the foreign (rat) therapeutic monoclonal antibody. Blood trough levels of CD4 and CD8 antibodies indicated that saturating doses were achieved. Although neither CD4 nor CD8 alone prolonged allograft survival (rejection by day 7), combination of CD4 and CD8 antibodies resulted in good graft function for a median of 14 days. The effect of removing circulating T lymphocytes was also assessed using a lytic Thy-1 monoclonal antibody. Alone Thy-1 had little effect but, when combined with CD4, the median allograft survival time was increased to 15.5 days. Reduction of the number of circulating T lymphocytes appears complementary to blockade of CD4 for immunosuppression, while blockade of CD4 combined with removal of CD8 also favours allograft survival.